Understand mental health impact of pandemic on sports medicine staff (Part 2). Issue 3 (1st June 2021) - Neal, Timothy; Quandt, Eric; Thornton, James; Tucker, James
Abstract : No one could have predicted in February of 2020 the new and stressful roles that athletic trainers and team physicians would assume in managing the COVID‐19 pandemic in intercollegiate athletics.